A relação do musico com o trabalho: quando o trabalho do musico passa de trabalho improdutível para trabalho produtível em Belo Horizonte - Valmir Alcântara Alves (2018)
This thesis aims to analyze the current processes and musicians relations with specific human activity in producing sound as a job, from the investigation of music production processes in the city of Belo Horizonte, as an expression of the activity. In order to understand such autonomous processes in an analysis of the social, political, economic and cultural context it is necessary we create a thesis which contributes to the dialectic of unproductive and productive work in a dynamic job - that of the musician. Our intention was to build a thesis that constituted a study seeking to articulate the general process of capitalist production to the specific work of the musician. The historical setting of the exploitation of the musician workforce allows capitalism to create new classifications as a kind of make-up for the exploitation. There are laws to encourage culture, which has already set an economic model of artistic production in Brazil, named new creative economy. It comes from adapting such work relationships in a way to ensure for itself and expand its profit margin. Recent specific surveys on the economy around art, produced by João Pinheiro Foundation about the cultural sector in the city of Belo Horizonte, directly contributes to our study, which seeks to deepen the relationship between the art worker, especially the musician, and his precarious conditions. We checked, briefly, the limitations of conditions of contracts and payments. Our study produces knowledge that dialogues with the dichotomy between productive labor and unproductive labor, enabling us to formulate hypotheses about overcoming that mode of production whose weakness and strengths rest contradictory within its crises. We review those two categories and the classification of formulated work by Marx, which can be used to build the hypothesis that we unveil. The thesis when human activity work in producing sound goes from unproductive work to productive can be demonstrated due to the inconsistency in the changing sociocultural and market paradigms of modern times. There is great difficulty in the case of the art of identifying the unproductive labor or productive work only by the characterization of surplus value.